2008
DOI: 10.1002/jsfa.3455
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and toxicological evaluation of wheat grown on soils with or without fly ash treatment

Abstract: BACKGROUND: Fly ash disposal has recently posed a huge environmental problem due to storage, apart from apprehension about possible contamination of soil, crop produce and ground water with toxic trace and heavy metal and radio nuclides. The purpose of the present study was to evaluate nutritional and toxicological aspects of wheat grown on soils treated with fly ash. Wheat was grown on soils with fly ash (200 t ha −1 ) and without fly ash at two different geographical locations in India. One kilogram each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
4
1
0
Order By: Relevance
“…All wheat cultivars analysed showed an ash content inside the interval 1.40% and 1.88%, which values were obtained for Vitrón and Español cultivars, respectively. Ash mean content obtained in this paper is in agreement with data reported in the literature (RANDHAWA et al, 2002;SERENA & KNUDSEN, 2007;KANDLAKUNTA et al, 2009;HAGER et al, 2012;ANDERSSON et al, 2013). The fat concentration varied between 0.73% and 1.41% obtained in De la tierra and Vitrón cultivars, respectively.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…All wheat cultivars analysed showed an ash content inside the interval 1.40% and 1.88%, which values were obtained for Vitrón and Español cultivars, respectively. Ash mean content obtained in this paper is in agreement with data reported in the literature (RANDHAWA et al, 2002;SERENA & KNUDSEN, 2007;KANDLAKUNTA et al, 2009;HAGER et al, 2012;ANDERSSON et al, 2013). The fat concentration varied between 0.73% and 1.41% obtained in De la tierra and Vitrón cultivars, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The fat concentration varied between 0.73% and 1.41% obtained in De la tierra and Vitrón cultivars, respectively. The fat content found by us was lower than the data published by most authors (SIKA et al, 1995;RANHOTRA et al, 1996;KANDLAKUNTA et al, 2009;DI SILVESTRO et al, 2012;HAGER et al, 2012;ANDERSSON et al, 2013), although similar to those reported by RAGAEE and co-workers (2006). Total phenolic concentrations were fairly constant among the cultivars considered.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Because most of the FAs from India are alkaline in nature (Mishra and Shukla, 1986a, b), leaching of toxic constituents is less of a concern when they are being used in agriculture and silviculture (Khanra et al, 1998;Ram et al, 1999bRam et al, , 2000Ram et al, , 2007aKhan et al, 2000;Mukherjee and Zevenhoven, 2006). Kandlakuntha et al (2009) found no adverse effects on haematological, biochemical or histopathological parameters when rats were fed wheat grown on fly ash. They concluded that wheat grown on FA-treated soils may be safe for human consumption.…”
Section: Indian Fasmentioning
confidence: 95%